Sustainable intensification and the African smallholder farmer - Vanlauwe, Bernard; Coyne, Danny L.; Gockowski, J.; Hauser, S.; Huising, J.E.; Masso, C.; Nziguheba, Generose; Schut, Marc; Asten, Piet J.A. van (Elsevier, 2014)
Sub-Saharan Africa needs to produce more food, feed, and fiber to support its growing population and intensification of smallholder agriculture is a crucial component of any strategy towards this goal. Sustainable Intensification (SI) acknowledges that enhanced productivity needs to go hand in hand with the maintenance of other ecosystem services and enhanced resilience to shocks. A very diverse group of smallholders dominate SSA agriculture, with large heterogeneity in socio-technical conditions, famer typologies, production objectives, and the biophysical environment. This potentially generates a multitude of pathways from the current low productivity based on nutrient mining to SI. The institutional context needs to be right for delivering the necessary goods and services underlying SI, ensuring inclusiveness across household types and facilitating local innovation.